A long range restriction map of the pseudoautosomal region by partial digest PFGE analysis from the telomere. - Rappold, G A (1988)
The analysis of partial digestion products extending from the telomere of the human X and Y chromosomes, visualised by hybridisation to a probe located close to the telomere, was used to establish a restriction map of the pseudoautosomal region. In this highly polymorphic region with a 10-fold elevated recombination frequency in males we identified site or methylation differences between 7 different in male and female cell lines and tissues, and derived an estimate of the size of the pseudoautosomal region of approximately 3 Megabases by comparing X and Y chromosomes. This size correlates well with previous estimates based on genetic arguments and argues against a strongly enhanced rate of exchange near telomeres in general. We identified a CpG rich and hypomethylated region within 500 kbp from the telomere, which might reflect structural features of mammalian telomeres, and a small number of (additional) CpG islands, which might represent candidate genes for the Turner phenotype in XO females.